5(3x-6)=-(x+7)+2x

Simple and best practice solution for 5(3x-6)=-(x+7)+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x-6)=-(x+7)+2x equation:


Simplifying
5(3x + -6) = -1(x + 7) + 2x

Reorder the terms:
5(-6 + 3x) = -1(x + 7) + 2x
(-6 * 5 + 3x * 5) = -1(x + 7) + 2x
(-30 + 15x) = -1(x + 7) + 2x

Reorder the terms:
-30 + 15x = -1(7 + x) + 2x
-30 + 15x = (7 * -1 + x * -1) + 2x
-30 + 15x = (-7 + -1x) + 2x

Combine like terms: -1x + 2x = 1x
-30 + 15x = -7 + 1x

Solving
-30 + 15x = -7 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-30 + 15x + -1x = -7 + 1x + -1x

Combine like terms: 15x + -1x = 14x
-30 + 14x = -7 + 1x + -1x

Combine like terms: 1x + -1x = 0
-30 + 14x = -7 + 0
-30 + 14x = -7

Add '30' to each side of the equation.
-30 + 30 + 14x = -7 + 30

Combine like terms: -30 + 30 = 0
0 + 14x = -7 + 30
14x = -7 + 30

Combine like terms: -7 + 30 = 23
14x = 23

Divide each side by '14'.
x = 1.642857143

Simplifying
x = 1.642857143

See similar equations:

| y+9=2y-60 | | y+3=x+6 | | 2y-60=y+9 | | x^4-4x^3-x-2=0 | | 2*-3-7y=17 | | Y+2=-5(x-1) | | 15+8t=3t | | 8r=3t+4 | | 1.96g-12=0.74 | | -5w^3-4w^2+7w+16=3 | | 3x-15+2x+25=180 | | 31.61=6g+3.65 | | 4.3=5.1-0.2x | | 2n^2+n-13=-3 | | 11n^2-6N+4=7 | | 5(4*7)+x=5 | | 50=-3x-7 | | 5.9=6.5-0.3x | | ln(4x)+ln(x)=1.5 | | 3(6-x)=30 | | -4+2a=10 | | 4+2a=10 | | -13n-67=-11 | | x^2+3x-c=0 | | 83=8w+35 | | 4u+15=75 | | .06(x)=3142 | | 18.5=-7.2f+97.7 | | 7x-10y=12 | | 2x+7x=20 | | 8(x-2)=2(2x-2) | | 10.6=h+3.4 |

Equations solver categories